Rancang Bangun Sistem Monitoring Suhu dan Pakan Pada Kandang Ayam Berbasis Internet Of Things mengunakan NODEMCU ESP8266 - Shofi Syarifudin; Rizky Mubarok; Edmud Ucok Armin (Journal of Electronic and Electrical Power Applications, 2021)
The development of technology in Indonesia is increasingly advanced along with the times. With the industrial era 4.0, it is easier for every job that humans do. Now more and more industries are using robots as a substitute for human labor. With the development of the times that have an impact on technological change and the creation of internet of things (IOT) technology which makes it easier for humans to do a job. In this study, the NODEMCU ESP8266 microcontroller was used as the implementation of controlling temperature, humidity and feed based on the internet of things (IOT). The data taken from these sensors can be accessed in real time on the web and Telegram bot via smartphone connected to the internet.